THE EQUATION OF MOVEMENT OF THEWORCING CONTAINER DURING VIBRO-MAGNETIC-ABRASIVE PROCESS OF SUPER HARD CERAMICS - Бурлаков, Виктор (SWorldJournal, 2022)
The paper considers the calculation of a dynamic model of a working container for processing superhard ceramics in order to determine the position of such a container at each point in space. Thus, knowing the position of the container, we will know the p